Long-Term Storage of Rabies Virus Fixed Strains L. Pasteur and CVS at Temperatures of –20 and –80°C Using Protective Media - Varianytsia, Viktoriia V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 169